Influence Of The Philosophers Ideas On Teaching Arabic In Light Of (Al-Tamayz) Al-Firharwi/ ØªØ£Ø«ÙŠØ±Ø£ÙÙƒØ§Ø± Ø§Ù„ÙÙ„Ø§Ø³ÙØ© Ø¹Ù„Ù‰ ØªØ¯Ø±ÛŒØ³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø¶ÙˆØ¡ ((Ø§Ù„ØªÙ…ÙŠØ²)) Ù„Ù„ÙØ±Ù‡Ø§Ø±ÙˆÙŠ - Saeed Rana, Hafiz Ahmed; Khalil, Abuzar (Ijaz Arabi Journal of Arabic Learning, 2021)
The rise of philosophy has coalesced with the start of the world, which means a "strategy". Whether that Strategy is linked to the teaching of a language or something else, and the only way to learn that strategy is through the thoughts of philosophers. This study is an attempt at the philosophy, philosophers, and strategy of their thinkings; whom' Abdul-â€˜AzÄ«z FirhÄrvÄ« has mentioned in his valuable manuscript Al-TamyÄ«z, and also this study will discuss the effects of applying these strategies on the teaching of Arabic Language that how to cultimate philosophical styles of study like;Analytical method, Deep Study Method, Traditional Method, Discusson Method, Practical Methodâ€™ within primary or secondary or higher education students.In addition, these methods will promote a technical understanding of Arabic Grammer among students.In this regard, 'Abdul-â€˜AzÄ«z FirhÄrvÄ« has selected some prominent philosophers inÂ  Al-TamyÄ«z. Further, it will highlight the selection of chosen philosophers as to why the thoughts of these philosophers have a possible and attainable effect on the teaching of the Arabic Language, and it will also discuss the influential importance of their work. Thus, this study will be beneficial for the teachers and trainers. Moreover, it will also become a landmark for the new researchers to link philosophy with Arabic language teaching.